Altares in the desert: The stone structures on the geoglyphs Nasca in Palpa - Reindel, Markus (2017)
In this article, we present the results of the excavactions conducted in severa! structures that were found in association with geoglyphs located in the Palpa Province, within the northern side of the Rio Grande Basin. Toe geoglyphs were built over slopes and plateaus that are placed within and long the Rio Grande, Palpa and Viseas Valleys. The reported data indicate that the construction of these geoglyphs started during the middle developmental stage of the Paracas Culture (ca. 500 B.C.) and ended with the final development of the Nasca Culture (A.O. 650). During this time, and specially during the Nasca time, the slopes and plateaus formed part of an active social landscape, where geoglyphs became the scenario for important festive and religious activities. Among them, activites realted to water and fertility cults were remarkable. These activities rnight have taken place in the stone structures associated with the geoglyphs.